Students’ Experience during the Integration of Traditional Games into the Elementary School Programm - Vasileva, Marina; Malinovski, Toni; Vasileva-Stojanovska, Tatjana; Trajkovik, Vladimir (Učiteljski fakultet; Sveučilišta u Zagrebu, 2018)
Even though the potential of game-based learning is widely recognized, we need to understand students to effectively integrate games in the classroom environment. This study aims to identify relevant factors that influence students’ experience during the integration of traditional children’s games into the elementary school program. The research involved 142 students from different elementary schools who participated in multiple learning sessions with pure game-based activities or games technologically enhanced with asynchronous/synchronous distance learning. A structural equation model was developed and tested using students’ responses to a survey conducted after each session. The results suggest that students’ experience is directly influenced by their motivation to participate in the new environment, their attitude during purely game-based classes, and technological behaviour during classes with distance learning activities. We also found that students of different ages showed similar subjective experience and identified a clear distinction between students’ views and learning outcomes during in-class gaming and asynchronous/ synchronous conditions.
Keywords: classroom games; elementary school; game-based learning; structural equation model; students’ experience